Distinct clinical characteristics of paraneoplastic optic neuropathy. Issue 6 (18th July 2018) - Xu, Quangang; Du, Wenjuan; Zhou, Huanfen; Zhang, Xin; Liu, Hongjuan; Song, Honglu; Wang, Xueqiong; Wei, Shihui
Abstract : Objective: Paraneoplastic optic neuropathy (PON) is relatively uncommon, and the visual outcomes and prognosis of this disease have not been well documented. The aim of this study was to investigate the clinical features and prognosis of antibody-mediated PON. Methods: Clinical data were retrospectively collected from hospitalised patients diagnosed with PON at the Neuro-Ophthalmology Department at the Chinese People's Liberation Army General Hospital from January 2015 to June 2017. Results: A total of seven patients (four females and three males,  13 involved eyes) were included with a mean age of 56.28±11.32 years (36–70 years). Simultaneous or early sequential bilateral eye involvement (5/7, 71.4%) was common in the patients with PON. Severe vision loss (≤0.1) was seen in 76.9% (10/13) of the eyes. There were 13 eyes in the acute phase of the disease, and six eyes presented with optic disc oedema. All patients had definite evidence of paraneoplastic-associated antibodies (three with serum positive for antiamphilphysin, one for anti-PNMA2 (Ma2/Ta), one for anti-Yo, one for anti-Ma2 and one for anti-CV2). All of the serum samples were negative for myelin oligodendrocyte glycoprotein antibody and two patients companied with seropositive for the aquaporin-4 antibody. Five patients had history of primary malignancy, including thyroid cancer, type B thymoma, testicular seminoma, cervical cancer and lung carcinoma. Two patients had positive paraneoplastic syndrome antibodies (anti-Yo and antiamphiphysin), but the solid tumour had not been found through a PET scan. Visual acuity in 9/13 (69.2%) eyes was below 0.1, and all of the patients survived to the follow-up with no metastatic lesions. Conclusions: PON is relative rare, with a predominance of bilateral involvement and more with a poor visual prognosis. Paraneoplastic antibody testing can contribute to the diagnosis of PON, distinct from other types of optic neuropathies, which can help doctors to find the primary cancer earlier to guide further treatment.